Direct arylation of tertiary amines via aryne intermediates using diaryliodonium salts. Issue 18 (2nd May 2018) - Zhang, Zhiang; Wu, Xunshen; Han, Jianwei; Wu, Wenjun; Wang, Limin
Graphical abstract: Highlights: A synthetic method of N -arylation of tertiary amines via benzynes with diaryliodonium salts was developed. The desire aromatic tertiary amines were synthesized in good yields of 55–91%. Diaryliodonium salts was used as the precursors of benzynes. Abstract: With a strategy by using diaryliodonium salts as the precursors of benzynes, direct N -arylation of tertiary amines with diaryliodonium salts was reported. Thus, the desired aromatic tertiary amines with a wide range of substituents were synthesized in moderate to excellent yields of 55–91%.